What motivates Sao Paulo citizens to use bicycles as a mode of transportation? A study in the light of the Goal-Framing Theory - Foltram, Felipe Fedrigo; Schnaider, Paula Sarita Bigio; Pelegrina, Juliano (Revista de Administração da UFSM, 2022)
Purpose – What motivates Sao Paulo citizens to use bicycles as a mode of transportation? To answer this question, we conceptually rely on the Goal-Framing Theory (Lindenberg, 2000), which seeks to understand how individual choices are made, and exogeneous variables such as climate and temperature which might influence in this decision. Design/methodology/approach – Empirically, we conduct a quantitative study, relying on primary data from 252 respondents and analyzed by means of logistic regression models, through which we obtained the likelihood of using bikes and the relative weights of each of the variables defined in our theoretical section. Findings – What motivates Sao Paulo residents are not economic reasons, but rather normative (doing what is right) or hedonic (the pursuit of personal satisfaction) aspects. In other words, we demonstrate that cyclists make this choice to comply with a norm, seeking for benefits to the environment and directly or indirectly to society, as opposed to benefitting individually from this decision. Practical implications – The research has implication for public policies. Originality/value – The study is one of the first to empirically test the Goal Framing Theory (Lindenberg, 2000) and, as far as we could tell, the first to assess the motivations for the use of bicycles as a means of transportation in Brazil and in Latin America.